2015
DOI: 10.1088/0953-2048/28/7/072002
|View full text |Cite
|
Sign up to set email alerts
|

Critical current density above 15 MA cm−2at 30 K, 3 T in 2.2μm thick heavily-doped (Gd,Y)Ba2Cu3Oxsuperconductor tapes

Abstract: A critical current (I c ) value of 3963 A/12 mm, corresponding to a critical current density (J c ) of 15 MA cm −2 has been achieved at 30 K, 3 T in the orientation of field parallel to the c-axis (B||c) in 2.2 μm thick film (Gd,Y)BaCuO tapes with 20 mol% Zr addition made by metal organic chemical vapor deposition. This J c level is more than a factor of four higher than the J c values of 7.5 mol% Zr-added tapes, which are an industry benchmark. The critical current values in a magnetic field of 3 T parallel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 27 publications
3
67
1
1
Order By: Relevance
“…3,16 Moreover, recent work has shown that large quantities (⩾10%) of second-phase additions are required to obtain the desired level of performance in superconductors. [17][18][19] Until now, such a large amount of second phase resulted in current blocking and the loss of crystallinity. 19,20 For REBCO superconductors, MOD has been shown to be amenable for growing extremely high performance materials [21][22][23][24][25][26] with high throughput; [27][28][29] however, the tailoring of NP inclusions is extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,16 Moreover, recent work has shown that large quantities (⩾10%) of second-phase additions are required to obtain the desired level of performance in superconductors. [17][18][19] Until now, such a large amount of second phase resulted in current blocking and the loss of crystallinity. 19,20 For REBCO superconductors, MOD has been shown to be amenable for growing extremely high performance materials [21][22][23][24][25][26] with high throughput; [27][28][29] however, the tailoring of NP inclusions is extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Until now, such a large amount of second phase resulted in current blocking and the loss of crystallinity. 19,20 For REBCO superconductors, MOD has been shown to be amenable for growing extremely high performance materials [21][22][23][24][25][26] with high throughput; [27][28][29] however, the tailoring of NP inclusions is extremely difficult. 30 Unlike PLD, the formation of NPs during MOD occurs before matrix formation; therefore, the NP size is not determined by crystalline strain but by diffusion, leaving little room for tailoring particle size compared with that of in situ processes, where growth dynamics affect the nanoparticle/nanorod morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable progress has been made in improving the in-field performance by thorough understanding of BZO nanorod self-assembly process and its effect on in-field performance using MOCVD. One particular aspect of interest was maximizing the lift factor (LF), defined as the ratio of I c at desired temperature/field and I c value at 77 K, self-field itself 1215 . Extensive optimization of the REBCO-BZO system has been done using MOCVD, in terms of dopant concentration, film microstructure, growth conditions and composition to achieve high in-field performance 13,1618 .…”
Section: Introductionmentioning
confidence: 99%
“…MOCVD is restricted by its inability to grow thicker films (>1 µm) in a single pass due to its poor temperature control and non-uniform flow distribution which causes a-grains to grow progressively with thickness 15,22,23 . The degradation of performance is at least in part due to this increase in fraction of a-axis oriented grains in thicker films.…”
Section: Introductionmentioning
confidence: 99%
“…At 4.2 K and 20 T in perpendicular field, industrially produced REBCO has attained record values of J E in excess of 800 A/mm 2 [20], and the target performance of Table I was achieved by several production routes. In addition, the J E potential does not seem to be fully exploited [21]. The REBCO superconducting layer has a thickness of one µm to a few µm, and a width of a few mm.…”
Section: Hts Materials Focusmentioning
confidence: 99%